Suggestions for the Work of Dental Hygienists and a Reflection of Health Insurance Charges according to Demographic Changes - Myung-Jin Lee; Sang-Hwan Oh (The Korean Society of Dental Hygiene Science, 2020)
iven that the demand for dental care for elderly individuals is expected to increase according to demographic changes, long-term roadmaps for the current health insurance system should be actively planned. The study aimed to investigate the health insurance system in Korea, compared to that of Japan, and suggest directions for the work of dental hygienists to provide basic data on efficient improvements in the health insurance system. Based on the collected data, the website was used to collect additional related data from Korea and Japan. The most common cause of death in Korea was malignant neoplasms, and most patients were hospitalized for diseases and disorders of the musculoskeletal system and connective tissue. Dental care covered by Korean medical insurance for individuals aged 65 years or older was treatment oriented, such as dentures and implants, while in Japan, treatment-intensive items, such as visiting a dental hygienist for guidance and provision of home-care professional oral hygiene treatment, were covered. The percentages of remaining teeth in Korea and the percentage of remaining 20 teeth were 68.9% in those aged 65 to 74 years and 51.2% in those aged 75 to 84 years in Japan. A strategy for promoting oral health among elderly individuals should be established, and a multilateral intervention approach is required to prevent oral problems from leading to deterioration of whole-body health. The role of dental hygienists in providing comprehensive assessment to elderly individuals is important. In order to provide systemic oral care, it is necessary to introduce oral care systems according to the national policy.